2019
DOI: 10.1002/hep.30294
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin‐2 Promotes Pathological Angiogenesis and Is a Therapeutic Target in Murine Nonalcoholic Fatty Liver Disease

Abstract: Angiogenesis contributes to the development of nonalcoholic steatohepatitis (NASH) and promotes inflammation, fibrosis, and progression to hepatocellular carcinoma (HCC). Angiopoietin‐2 (Ang‐2) is a key regulator of angiogenesis. We aimed to investigate the role of Ang‐2 and its potential as a therapeutic target in NASH using human samples, in vivo mouse models, and in vitro assays. Serum Ang‐2 levels were determined in 104 obese patients undergoing bariatric surgery and concomitant liver biopsy. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
123
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 103 publications
(128 citation statements)
references
References 44 publications
(105 reference statements)
4
123
1
Order By: Relevance
“…The authors further undertook elegant three-dimensional reconstruction imaging of the hepatic vasculature in those various groups of MCD diet-fed mice and demonstrated that L1-10 treatment, as either a preventive or a therapeutic intervention, reduced abnormal angiogenesis with decreased vascular density compared to placebo. (5) They also showed that L1-10 treatment reduced angiogenic signaling from cultured endothelial cells following lipopolysaccharide stimulation, confirming their observations that L1-10 reduces neoangiogenesis primarily through cell autonomous (i.e., endothelial) signaling. In a final series of studies, the authors returned to the streptozotocin-western diet model of NASH and asked if L1-10 would mitigate the development of HCC.…”
Section: See Article On Page 1087mentioning
confidence: 57%
See 4 more Smart Citations
“…The authors further undertook elegant three-dimensional reconstruction imaging of the hepatic vasculature in those various groups of MCD diet-fed mice and demonstrated that L1-10 treatment, as either a preventive or a therapeutic intervention, reduced abnormal angiogenesis with decreased vascular density compared to placebo. (5) They also showed that L1-10 treatment reduced angiogenic signaling from cultured endothelial cells following lipopolysaccharide stimulation, confirming their observations that L1-10 reduces neoangiogenesis primarily through cell autonomous (i.e., endothelial) signaling. In a final series of studies, the authors returned to the streptozotocin-western diet model of NASH and asked if L1-10 would mitigate the development of HCC.…”
Section: See Article On Page 1087mentioning
confidence: 57%
“…Administration of L1‐10 reduced inflammation, ballooning, and fibrosis in MCD diet–fed mice but did not change the degree of steatosis. The authors further undertook elegant three‐dimensional reconstruction imaging of the hepatic vasculature in those various groups of MCD diet–fed mice and demonstrated that L1‐10 treatment, as either a preventive or a therapeutic intervention, reduced abnormal angiogenesis with decreased vascular density compared to placebo . They also showed that L1‐10 treatment reduced angiogenic signaling from cultured endothelial cells following lipopolysaccharide stimulation, confirming their observations that L1‐10 reduces neoangiogenesis primarily through cell autonomous (i.e., endothelial) signaling.…”
mentioning
confidence: 72%
See 3 more Smart Citations